Teacher modeling for waste disposal: Preschool behavioral development in Makassar and Gowa, Indonesia - Rusmin, Muhammad; Lagu, Abd. Majid HR. (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Early childhood environmental interventions increasingly promote waste-disposal habits, yet limited community-based programs have combined teacher modeling, child-friendly waste infrastructure, and multidimensional behavioral assessment among preschool children. This community engagement program aimed to improve teachers’ waste-disposal behavior and modeling capacity while strengthening preschool children’s positive waste-disposal development in six kindergartens in Makassar and Gowa, South Sulawesi, Indonesia. A Participatory Action Research approach was applied through advocacy, focus group discussions, instrument assessment, enumerator training, baseline measurement, teacher-modeling training, school-based mentoring, post-intervention assessment, reflection, and program revision. Twelve teachers participated in the training, and each school received segregated waste bins for organic, inorganic, and hazardous waste with color-coded labels and visual illustrations. Teachers demonstrated significant improvements in modeling ability, knowledge, attitudes, and practices after the intervention, with all Wilcoxon signed-rank test results showing p < 0.001. Preschool children also showed significant improvements in cognitive, language, motor, social, and affective domains, with posttest scores exceeding pretest scores across all participating schools. The findings indicate that teacher modeling supported by accessible waste-disposal facilities can serve as a practical school-based environmental-health intervention for establishing positive habits during early childhood.